Animals, Plants and Afterimages The Art and Science of Representing Extinction - Bienvenue, Valerie (Berghahn Books, 2022)
The sixth mass extinction or Anthropocene extinction is one of the most pervasive issues of our time. Animals, Plants and Afterimages brings together leading scholars in the humanities and life sciences to explore how extinct species are represented in art and visual culture, with a special emphasis on museums. Engaging with celebrated cases of vanished species such as the quagga and the thylacine as well as less well-known examples of animals and plants, these essays explore how representations of recent and ancient extinctions help advance scientific understanding and speak to contemporary ecological and environmental concerns.